Countering Cultural Stigmatization in a Decolonized System of Inter-ritual Encounters in Aceh, Indonesia - Muhammad Maulana (Journal of Religion and Decoloniality, 2025)
This article examines how inter-ritual encounters in Aceh, Indonesia, serve as a decolonized system countering cultural stigmatization by challenging dominant narratives and reshaping religious boundaries through community-based interactions. Addressing prevalent perceptions of Aceh as socially exclusive due to its strong Islamic identity, this study emphasizes everyday interreligious engagements emerging through ritual presence, communal participation, and reciprocal social practices. Utilizing qualitative data drawn from digital archives, online media, and visual documentation, the research explores how Muslim communities participate in Hindu Tamil and Chinese festivals, while non-Muslim residents engage with Islamic spaces and events. These interactions, such as observing public rituals, providing technical assistance, food sharing, and visiting sacred sites, represent localized forms of mutual recognition rooted in community proximity and historical coexistence. The findings demonstrate that these inter-ritual practices constitute relational strategies affirming coexistence and rejecting externally imposed stigmas of intolerance. Framed within a decolonial perspective, the article highlights how everyday ritual interactions reflect alternative epistemologies grounded in lived social realities rather than institutional or legal frameworks. The study contributes to broader discussions of interreligious dynamics, suggesting its relevance to other global contexts where religious majorities significantly shape public life and interreligious relations, thus expanding the understanding of cultural coexistence and mutual respect in diverse religious environments.